Casein Kinase 2 Signaling in White Matter Stroke - Nguyen, Hung; Zhu, Wenbin; Baltan, Selva (Frontiers in Molecular Biosciences, 2022)
The growth of the aging population, together with improved stroke care, has resulted in an increase in stroke survivors and a rise in recurrent events. Axonal injury and white matter (WM) dysfunction are responsible for much of the disability observed after stroke. The mechanisms of WM injury differ from gray matter and change with age. Therefore, an ideal stroke therapeutic must not only restore neuronal and axonal function when applied before or after a stroke, but it must also protect across age groups. Casein kinase 2 (CK2), is expressed in the brain, including WM, and is regulated during development and numerous disease conditions such as cancer and ischemia. CK2 activation in WM mediates ischemic injury via the Cdk5 and AKT/GSK3β signaling pathways. Consequently, CK2 inhibition using the small molecule inhibitor CX-4945 (Silmitasertib) correlates with preservation of oligodendrocytes, conservation of axon structure and axonal mitochondria, leading to improved functional recovery. Remarkably, CK2 inhibition promotes WM function when applied after ischemic injury by specifically regulating the AKT/GSK3β pathways. The blockade of the active conformation of AKT confers post-ischemic protection to young and old WM by preserving mitochondria, suggesting a common therapeutic target across age groups. Using a NanoString nCounter® miRNA expression profiling, comparative analyses of ischemic WM with or without CX-4945 treatment reveal that miRNAs are expressed at high levels in WM after ischemia and CX-4945 differentially regulate some of these miRNAs. Therefore, we suggest that protective functions of CX-4945 against WM injury maybe mediated, in part, through miRNA regulation. Silmitasertib is currently being used in clinical trials for cancer and Covid patients; therefore, it is plausible to consider the potential benefits of CK2 inhibitors for stroke patients.